Evaluation of Mango Leaf Extract as a Natural Preservative for Enhancing the Shelf Life and Quality of Milkfish - Nurhayati B; Yahdiel Ronrong; Nani Kurnia; Alimuddin Ali (Bionature, 2025)
This study investigates the potential of mango leaf extract as a natural preservative to extend the shelf life of milkfish (Chanos chanos) during storage. The extract was prepared using a standardized method and applied to milkfish fillets, followed by an analysis of its effects on microbial growth, sensory attributes, and overall shelf life. The milkfish samples were stored in the refrigerator, and periodic evaluations of sensory quality, including color, texture, odor, and taste, as well as microbiological parameters, were conducted. The findings of this study demonstrate that mango leaf extract effectively inhibits microbial growth and shows potential as a natural preservative for milkfish. The use of 1% mango leaf extract, especially ethanol-based, exhibited the highest microbial inhibition, significantly extending the shelf life and maintaining the quality of milkfish compared to untreated samples. These findings suggest that mango leaf extract can be an effective, natural alternative to chemical preservatives in extending the shelf life of milkfish, offering a promising solution for sustainable seafood preservation.